Digital light processing porous TPMS structural HA & akermanite bioceramics with optimized performance for cancellous bone repair. Issue 3 (1st February 2022) - Hua, Shuai-Bin; Yuan, Xi; Wu, Jia-Min; Su, Jin; Cheng, Li-Jin; Zheng, Wen; Pan, Ming-Zhu; Xiao, Jun; Shi, Yu-Sheng
Abstract: In recent years, amorphous bioglass is used to improve the bioactivity of HA (Ca10 (PO4 )6 (OH)2 ). Nevertheless, bioglass crystallizes and reacts with the matrix to form a complex phase composition during sintering, resulting in an unclear mechanism for tailoring the properties of HA bioceramics. In this work, TPMS structural HA ceramics fabricated by digital light processing (DLP) were doped by akermanite (Ca2 MgSi2 O7 ) to better tailor the porosity, bioactivity and mechanical strength. After sintering above 1000 °C, Mg 2+ ions from akermanite substitute Ca 2+ ions in HA, leading to the decomposition of HA into β-TCP. This process increases the porosity of bioceramics. Additionally, liquid phases sintering caused by akermanite gives rise to the densification and enhancement of grain bonding, thereby reinforcing the mechanical strength of scaffolds. For in vitro bioactivity, as the content of akermanite increases from 0 wt% to 20 wt%, carbonated hydroxyapatite firstly deposits onto the surfaces of scaffolds and then disappears, because excessive Mg 2+ prevent the hydroxyapatite crystallization. Finally, bioceramics with 5 wt% and 10 wt% of akermanite and sintering at 1100 °C exhibit a high porosity of over 80% and an appropriate compressive strength of over 2 MPa, while achieving an enhanced in vitro bioactivity and good biocompatibility. After optimization, this kind of porous scaffolds can be well applied to the repair of cancellous bone defect.